The future of academic publishing: application of the long-tail theory - Gould, Thomas H. P. (My University, 2013)
Print academic journals are dead. As we watch large metropolitan newspapers fail (as are many small town newspapers), the same economic forces are driving online scholarly publishing. This phenomenon is more than print journals going online. The options available with new low-cost online publishing software and the rise in the ability to use ratings from user generated content suggest more near-term changes are likely. Many of the outcomes are unsettled: the economics of online publishing; the standards for peer review, rank, and tenure; and the very nature of scholarly publishing itself. What is certain, however, is that the economics of online academic publishing—modeled via Anderson’s Long Tail Theory—will make it possible to provide greater access, more collaboration, and, ultimately, improved research and researchers. Universities acting as publishing centers with their e-reserves will be expected to change their faculty evaluations, providing greater academic rewards for those who act as editors, reviewers, and proofreaders within this new born-online and only-online world.
Keywords: Academic publishing; Paradigm shift; Online academic research journals; Online publishing